Do Racial and Ethnic Disparities in Savings and Job Loss during COVID-19 Explain Disparities in Housing Hardships? A Moderated Mediation Analysis. Issue 1 (November 2021) - Grinstein-Weiss, Michal; Chun, Yung; Roll, Stephen; Jabbari, Jason
Despite the array of public programs offered to help households mitigate the economic impacts of the COVID-19 pandemic, many still needed to rely on savings, credit, or other assets to make ends meet. This reality may exacerbate existing social and economic inequities because racial and ethnic minorities often have lower access to assets and credit than white households. We use longitudinal national survey data to explore the extent to which different racial and ethnic groups experienced housing hardships during the pandemic, the role of liquid assets in mediating housing hardship, and whether job/income loss moderated the relationship among race/ethnicity, liquid assets, and housing hardship. We find that liquid assets significantly mediated the relationship between race/ethnicity and housing hardships and that the effect was stronger for those who lost jobs or incomes as a result of COVID-19.